Elimination of the light soaking effect and performance enhancement in perovskite solar cells using a fullerene derivative. Issue 7 (17th June 2016) - Shao, Shuyan; Abdu-Aguye, Mustapha; Qiu, Li; Lai, Lai-Hung; Liu, Jian; Adjokatse, Sampson; Jahani, Fatemeh; Kamminga, Machteld E.; ten Brink, Gert H.; Palstra, Thomas T. M.; Kooi, Bart J.; Hummelen, Jan C.; et al.
Abstract : The higher dielectric constant and electron donating properties of PTEG-1 electron extraction layer synergistically helps to eliminate the light soaking effect and enhance device performance. Abstract : In this work, we investigate how electron extraction layers (EELs) with different dielectric constants affect the device performance and the light-soaking phenomenon in hybrid perovskite solar cells (HPSCs). Fulleropyrrolidine with a triethylene glycol monoethyl ether side chain (PTEG-1) having a dielectric constant of 5.9 is employed as an EEL in HPSCs. The commonly used fullerene derivative [60]PCBM, which has identical energy levels but a lower dielectric constant of 3.9, is used as a reference. The device using PTEG-1 as the EEL shows a negligible light soaking effect, with a power conversion efficiency (PCE) of 15.2% before light soaking and a minor increase to 15.7% after light soaking. In contrast, the device using [60]PCBM as the EEL shows severe light soaking, with the PCE improving from 3.8% to 11.7%. Photoluminescence spectroscopy and impedance spectroscopy measurements indicate that trap-assisted recombination at the interface between the hybrid perovskite and the EEL is the cause of the light soaking effect in HPSCs. The trap-assisted recombination is effectively suppressed at the perovskite/PTEG-1 interface, while severe trap assisted recombination takes place at the perovskite/[60]PCBM interface. We attributed these experimental findings to the fact that the higher dielectric constant of PTEG-1 helps to screen the recombination between the traps and free electrons. In addition, the electron donating side chains of PTEG-1 may also contribute to the passivation of the electron traps. As a consequence, the devices using PTEG-1 as the EEL display a considerable increase in the efficiency and a negligible light soaking effect.